2018
DOI: 10.1002/asia.201801087
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Dual Fuel Cell Electrocatalysis with Trimetallic PtPdCo Mesoporous Nanoparticles

Abstract: The facile preparation of platinum-based catalysts with designed compositions and structures is of great importance for fuel cells. In this work, a one-pot method is developed to synthesize monodispersed trimetallic PtPdCo mesoporous nanoparticles (PtPdCo MNs) with uniform morphology and size. The proposed synthetic method does not require any hard template or organic solvent, which greatly simplifies the preparation procedure. PtPdCo MNs, with a highly porous structure, exhibit enhanced electrocatalytic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 60 publications
(115 reference statements)
2
18
0
Order By: Relevance
“…For comparison, the experiment has been carried out without the addition of F127 and the obtained sample aggregated severely (Figure S5). So F127 could not only act as structure‐directing agent, but also effectively prevent the agglomeration of the catalysts, which is in accordance with our previous work . The reduction ability of AA will be decreased by HCl, which is contribute to the formation of mesoporous structure.…”
Section: Resultssupporting
confidence: 86%
“…For comparison, the experiment has been carried out without the addition of F127 and the obtained sample aggregated severely (Figure S5). So F127 could not only act as structure‐directing agent, but also effectively prevent the agglomeration of the catalysts, which is in accordance with our previous work . The reduction ability of AA will be decreased by HCl, which is contribute to the formation of mesoporous structure.…”
Section: Resultssupporting
confidence: 86%
“…Therefore, it is necessary to introduce a second metal into Pt‐based catalysts by forming an alloyed structures to improve their catalytic activity. Recently, it has been reported that Pt–Ag, Pt–Cu, Pt–Pd and Pt–Au bimetallic catalysts exhibit better catalytic performance than pure Pt catalysts in many research fields . Among them, Pt–Au bimetallic catalysts have aroused intensive research.…”
Section: Methodssupporting
confidence: 63%
“…Moreover, other two Pt‐M alloy (M=Pd, Cu) cocatalysts with the same 0.5 wt % loading amount on TiO 2 were prepared via the similar loading method, and the relative XPS results are illustrated in Figure S3 and Figure S4. In Pt‐Pd alloy, the binding energy positions of Pd 4f peaks at 334.0 and 339.7 eV are corresponding to the Pd 4f 7/2 and 4f 5/2 , respectively, indicating the metallic form of Pd . The XPS spectrum of Pt 4f presents binding energies of 69.7 and 73.1 eV, which can correspond to Pt 4f 7/2 and 4f 5/2 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Despite extensive reports on 1D Pt‐based nanomaterials, most of them show smooth surfaces . Owing to a large accessible surface area, efficient mass transport capacity, and more active sites, mesoporous nanostructures exhibit excellent catalytic properties in various electrochemical applications . Therefore, the fabrication of 1D Pt‐based tubular nanomaterials with mesoporous structures is expected to enhance the catalytic performance for the MOR.…”
Section: Introductionmentioning
confidence: 99%
“…[49][50][51] Owingt oalarge accessible surface area, efficient mass transport capacity,a nd more active sites, mesoporous nanostructures exhibit excellent catalytic properties in various electrochemicala pplications. [52][53][54][55] Therefore,t he fabrication of 1D Ptbased tubularn anomaterials with mesoporous structures is expectedt oe nhance the catalytic performance for the MOR. It is highly desired to develop as imple and effective methodf or preparing 1D Pt-based mesoporous nanotubes (MNTs).…”
Section: Introductionmentioning
confidence: 99%